A Review of Generalizable Transfer Learning in Automatic Emotion Recognition - Feng, Kexin; Chaspari, Theodora (Frontiers in Computer Science, 2020)
Automatic emotion recognition is the process of identifying human emotion from signals such as facial expression, speech, and text. Collecting and labelling such signals is often tedious and many times requires expert knowledge. An effective way to address challenges related to the scarcity of data and lack of human labels, is transfer learning. In this manuscript, we will describe fundamental concepts in the field of transfer learning and review work which has successfully applied transfer learning for automatic emotion recognition. We will finally discuss promising future research directions of transfer learning for improving the generalizability of automatic emotion recognition systems.